UJI BIOAKTIVITAS EKSTRAK DAUN SUREN (TOONA SINENSIS) TERHADAP MORTALITAS LARVA PLUTELLA XYLOSTELLA PADA TANAMAN SAWI HIJAU - KURNIAWAN, NISA (LenteraBio: Berkala Ilmiah Biologi, 2013)
The research aimed to determine the content of secondary metabolites in the leaves suren using phytochemical profile test and to determine the effect of various concentrations of leaf suren extract on mortality instar II of Plutella xylostella larvae. This research conducted in green house biology majors FMIPA UNESA with used Randomized Block Design (RBD). Suren leaves extract concentrations used were 6%, 8%, and 10%. Research data were phytochemical profiles that were analyzed descriptively, whereas the mortality of larvae of Plutella xylostella was tested by normality test prior to the test of one-way ANOVA followed by LSD test (Least Significant Difference). Phytochemical profiles obtained secondary metabolite alkaloids, flavonoids, steroids/triterpenoids and saponins, whereas mortality data showed that treatment with a concentration of 10% gave the highest influence on the mortality of Plutella xylostella of 86.3%.   Key words: bioactivity; suren leaf extracts, mortality; Plutella xylostella; green mustard